2021
DOI: 10.1108/dprg-03-2021-0046
|View full text |Cite
|
Sign up to set email alerts
|

Perceived effectiveness of e-governance as an underlying mechanism between good governance and public trust: a case of Indonesia

Abstract: Purpose This study aims to investigate the association of perceived accountability, perceived responsiveness and perceived transparency, and public trust in local government. Additionally, mediation of the perceived effectiveness of e-governance was also tested between these relationships. Design/methodology/approach Using a quantitative cross-sectional field survey, primary data was collected at local administration levels from two cities in Indonesia. The final data set of 355 respondents was then analyzed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 63 publications
(84 reference statements)
2
17
1
1
Order By: Relevance
“…In contrast, trust is a more subjective or general concept that can contribute to the police's good or bad performances (Madon & Murphy, 2021). Citizens' satisfaction has been reported as a significant predictor of their trust level in government officials based on good governance practices (Hartanto et al, 2021b). Likewise, research reveals that when citizens are satisfied with the services that government institutions provide and believe that government officials are working in the public's best interest, they start trusting such institutions (Pryce & Gainey, 2022).…”
Section: Citizens' Satisfaction and Trust In Policementioning
confidence: 99%
“…In contrast, trust is a more subjective or general concept that can contribute to the police's good or bad performances (Madon & Murphy, 2021). Citizens' satisfaction has been reported as a significant predictor of their trust level in government officials based on good governance practices (Hartanto et al, 2021b). Likewise, research reveals that when citizens are satisfied with the services that government institutions provide and believe that government officials are working in the public's best interest, they start trusting such institutions (Pryce & Gainey, 2022).…”
Section: Citizens' Satisfaction and Trust In Policementioning
confidence: 99%
“…Citizens' political trust means they believe in their elected governments' transparency, responsiveness, and accountability (Hartanto et al, 2021a;Mansoor, 2021). Researchers have shown that citizens' trust in the government highly depends upon their perceptions of the elected officials (Han et al, 2021;Hartanto et al, 2021b). These perceptions are developed based on various factors, including politicians' personalities, attitudes, and behaviors (Ulbig, 2007).…”
Section: Political Communication Political Efficacy Political Ideolog...mentioning
confidence: 99%
“…The time spent online represents how frequently an individual visits various social networking sites daily to weekly (Mansoor, 2021) and how many hours an individual surfs on social networking sites daily (Hartanto et al, 2021). These search reports are based on the increasing use of digital technologies, and the number of cybercrime victimization cases is increasing continuously (Nalaka & Diunugala, 2020).…”
Section: Time Spent Online Fear Of Terrorism and Fear Of Cyberterrorismmentioning
confidence: 99%